2017
DOI: 10.26417/ejes.v9i1.p25-33
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship with Ad Clicks and Purchase Intention: An Empiricial Study of Online Consumer Behaviour

Abstract: This study examines the ads on social media and word of mouth marketing lead to ad clicks. Motivation, congruity, attitudes to ad on social media and word of mouth marketing lead to ad clicks, which respectively affect purchase intention in research model. The study aims to develop an understanding of how ad clicks affect to purchase intention on social media. Findings of the study presents the importance of consumer behaviour to use of social media and to purchase intention among Turkish consumers. Consequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
4
5
0
Order By: Relevance
“…Furthermore, the current study found that ACR has a positive influence on both PI and OBB. This finding is in line with Chen et al (2021), Erdem et al (2017), Mir (2018),Mir, Haider, andSharjeel (2021). These studies identified that once users click social media ads, it influences both their intentions and actual online purchasing behavior.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Furthermore, the current study found that ACR has a positive influence on both PI and OBB. This finding is in line with Chen et al (2021), Erdem et al (2017), Mir (2018),Mir, Haider, andSharjeel (2021). These studies identified that once users click social media ads, it influences both their intentions and actual online purchasing behavior.…”
Section: Discussionsupporting
confidence: 91%
“…Another significant finding is that IVM has a direct influence on users' ACR. It is consistent with Erdem et al (2017) and Mir (2018). These studies found a direct association between users' social media usage motivations and their ACR.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations